STUDI TENTANG PELAKSANAAN HAK INISIATIF DPRD KUTAI KARTANEGARA PERIODE 2014-2018 - Efri Novianto; Salehuddin Salehuddin (Yogyakarta State University, 2019)
As an element of local government organizers, the DPRD is demanded to play an active role in carrying out its functions. One of the important functions of the DPRD is the formation of regional regulations together with the Regional Head. For the implementation of this function, the DPRD was given the right of initiative to submit a draft Regional Regulation. From the results of the study, the implementation of the DPRD Kutai Kartanegara initiative rights for the period 2014-2018 has been implemented well, but it is not optimal because on average only 14.63% has been passed into a Regional Regulation. In theory, the factors that influence the implementation of the DPRD initiative rights are education, experience and data / information factors, but this has been overcome by the existence of an Expert Team / Expert Group, workshops or training to increase the capacity of the DPRD and the Academic Script in each Design Regional Regulation submitted to the DPRD, so that it is no longer a limiting factor. The obstacles to the implementation of the DPRD's role are more due to political factors, budget support and consistency of regulations.